Barriers and facilitators of incorporating Ubuntu principles in the integrated management of childhood illness - Felicia O. Meno; Fhumulani M. Mulaudzi; Nombulelo V. Sepeng (African Journal of Primary Health Care & Family Medicine)
Background: Success in incorporating Ubuntu principles in the integrated management of childhood illness (IMCI) requires collaboration between health professionals and families and assistance from their communities. Despite this, the literature reviewed is silent about exploring caregivers’ perspectives regarding the barriers and facilitators of incorporating Ubuntu principles in managing childhood illness.